2012
DOI: 10.1134/s1063771012040057
|View full text |Cite
|
Sign up to set email alerts
|

A complex of analytical models for predicting noise in an aircraft cabin

Abstract: A series of analytical calculated models for predicting the noise in an aircraft cabin is developed: an orthotropic model, a model with discrete frames, a model with discrete stringers, a model with isolated cells, and a model with a cross system of discrete ribs. The analytical solution is constructed on the basis of the method of space harmonic expansion. Vibrations are represented in the form of double trigonometric series. Strict periodicity allows dividing the series into a large number of independent gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…We evaluate the noise suppression achieved in the cabin of a propeller airplane by stopping some of the frames. The acoustic part of the problem is omitted in this paper, because it is described in our previous publications [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…We evaluate the noise suppression achieved in the cabin of a propeller airplane by stopping some of the frames. The acoustic part of the problem is omitted in this paper, because it is described in our previous publications [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…(1), we obtain (2) where P is Fourier transformation p, analysis of how the critical layer affects noise propaga tion in plane parallel flows can be found in [21]. At the edge of the boundary layer r = r b , the equality of the solution obtained in the boundary layer region and the constant flow region should be satisfied, as well the as equality of their first derivatives, i.e., (3) where P BL is the solution within the boundary layer such that P BL (r f ) = 1 and (r f ) = 0; γ m is a constant. System of equations (3) establishes a relationship between coefficients a m , b m , and γ m , which makes it possible to express the amplitude of the scattered wave b m and the amplitude of the sound field within the boundary layer γ m by means of the amplitude of the incident field a m :…”
mentioning
confidence: 99%
“…The influence of the boundary layer has been studied mainly in relation to simulation of acoustic loads on the fuselage surface, which are necessary for deter mining noise in an aircraft's cabin (the problem of noise simulation in an aircraft cabin has been eluci dated in [2][3][4]). So, in [5][6][7], the influence of the boundary layer was considered in the simplest case of plane waves and a two dimensional boundary layer on an infinite plane, and it was shown that the boundary layer can exert a significant effect on the acoustic load at the surface of a body.…”
mentioning
confidence: 99%
“…A method of calculating noise in a cabin based on analytical models for calculating vibrations of a regu larly supported shell (a fragment of plane fuselage) was described in [1][2][3][4]. A model taking into account the discreteness of all ribs (both stringers and bulkheads) is the most interesting.…”
mentioning
confidence: 99%
“…A method for solving a limited shell taking into account all three components of dis placement of the shell and the corresponding relations was presented in [2,3]. We also gave the expressions [4] for a simplified problem of vibrations of infinite closed cylindrical shell taking into account only the normal component of displacement.…”
mentioning
confidence: 99%